2003
DOI: 10.2527/2003.8181911x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DGAT1 variants on milk production traits in German cattle breeds1

Abstract: Various QTL mapping experiments led to the detection of a QTL in the centromeric region of cattle chromosome 14 that had a major effect on the fat content of milk. Recently, the gene encoding diacylglycerol O-acyltransferase (DGAT1) was proposed to be a positional and functional candidate for this trait. This study investigated the effects of a nonconservative lysine to alanine (K232A) substitution in DGAT1, which very likely represents the causal mutation, on milk production traits. Existing granddaughter des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
151
4
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(195 citation statements)
references
References 13 publications
36
151
4
4
Order By: Relevance
“…The intermediary heredity on the locus has been assumed. The present results are in accordance with those of THALLER et al (2003), , GRISART et al (2002), WINTER et al (2002), and WELLER et al (2003. Based on the paper and repeated results of other authors, the locus of DGAT1 is of great significance in breeding.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…The intermediary heredity on the locus has been assumed. The present results are in accordance with those of THALLER et al (2003), , GRISART et al (2002), WINTER et al (2002), and WELLER et al (2003. Based on the paper and repeated results of other authors, the locus of DGAT1 is of great significance in breeding.…”
Section: Methodssupporting
confidence: 81%
“…Afterwards, the frequency rose by selection, since from the 50s´ milk fat has been prefered. THALLER et al (2003) give the frequency of the allelic variant coding for Lysine in the German Holstein of 0.548; similarly PAREEK et al (2005) found in young sires of Polish Black and White cattle, traditionally upgraded with the American Holstein breed, a frequency of the allele DGAT1 K of 0.68, in sires in artificial insemination of 0.60, and in cows of 0.48; rather more than in our groups. By contrast, WELLER et al (2003) in Israeli Holstein cows give a frequency of 0.09, in sires of 0.16.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Situated on BTA14, the DGAT1 gene encodes 489 amino acids and comprises 17 exons. By sequencing the bovine DGAT1 gene, a non-conservative lysine to alanine substitution was observed at position 232 (K232A) and seems to influence the major milk production traits, such as milk yield and milk composition (Grisart et al 2004;Thaller et al 2003;Winter et al 2002). Winter et al (2002) observed that the lysine variant is associated with greater milk fat content than the alanine variant.…”
Section: Molecular Approachmentioning
confidence: 99%
“…The effect of this mutation was highly significant for all milk production traits in and then the all hypotheses i with i Յ î will be rejected. This procedure guarantees that FDR Յ (m 0 /m )q (Benjamini and German Holsteins (Thaller et al 2003), with a substan- between 0.36 and 0.9 genetic standard deviations. The estimated widths of the confidence intervals (Ta-…”
mentioning
confidence: 99%